Angel investments of small family business entrepreneurs: cross-country evidence - Viviana Fernandez (Financial Innovation)
Abstract Recent literature has focused on the venture capital investments of large family firms made through their family offices. However, evidence regarding informal venture capital provided to nascent entrepreneurs by small family businesses is scant. I contribute to the literature by modeling the angel investments of about 30,000 family and non-family business entrepreneurs across 49 countries, who contributed about $64 million to businesses started by other entrepreneurs over a 3-year period. Based on this sample, I conclude that in countries with higher rates of small family businesses, angel investors are likely fewer, and the amounts invested in start-ups are also lower. Furthermore, I conclude that the owners/managers of small family businesses invest comparatively less capital in start-ups, irrespective of family relationships. I infer that this is attributable to the financing preferences of family businesses, which favor the use of internal resources for their continuity and the growth of their family capital.